(untitled) (Research, Society and Development, 2021)
In the present study, we conducted a survey on ethnobotanical information of chemical-pharmacological interest, which was acquired via on-site interviews using semi-structured questionnaires with informants in the community in Mucuri Basin in Minas Gerais, Brazil. 184 interviews were conducted with residents with 102 botanical species in approximately 87 genera and 41 families cited. In addition, respiratory system diseases were the most cited, accounting for 26.35% of the cases cited. Lippia alba (lemon balm) was the most cited species with a corrected popular use concordance of about 86.11%. The results suggested that vegetables are important therapeutic resources for the population. Such ethnobotanical studies are fundamental for the understanding and conservation of local culture with regard to the exploitation of medicinal plants. The findings of the present study contribute to the documentation of medicinal species in a Brazilian state characterized by mining, which implies the suppression of vegetation growth or the impairment of regeneration, which could lead to the disappearance of critical and invaluable plant species. The preservation of ethnobotanical knowledge is vital in areas with high human activity and areas undergoing deforestation.